Numerical and experimental studies on propulsion performance of a novel tandem paddles propulsor - Longqing Xin; Peng Liu; Huajun Li; Siqi Wang; Yuhua Lyu; Yaqian Li; Guodong Feng (Journal of Ocean Engineering and Science, 2025)
Normally, small unmanned vessels used to clean floating litter on water adopt a paddle wheel as a propulsor to satisfy its shallow-draft requirements; however, this type of propulsor has bulky structures and inefficient propulsion. In this study, a novel tandem paddles propulsor (TPP) was developed, and its propulsion performance was analyzed and compared with that of a paddle wheel propulsor (PWP). Using the RNG k-ε turbulence model and sliding grid technique, the hydrodynamic performance of the PWP was simulated in computational fluid dynamics (CFD) software to verify the reliability of the numerical method. Subsequently, the propulsion performances of the two types of propulsors were simulated with different immersion depths and advanced coefficients, and the differences in their mechanical characteristics and flow field evolution were discussed and compared. The results indicate that the proposed TPP generates 2.75 times more thrust and 1.99 times greater efficiency than the PWP, exhibiting superior propulsion capability in shallow-draft vessels.